PRINCE SVYDRYGAILO IN HALYCH AND THE FIRST WRITTEN MENTION OF KALUSH - STASIUK, Andrii (Halych. Scientific work collection, 2020)
The article is devoted to the little-known episode of the stay of the Lithuanian prince Svydrygailo Olgerdovych in Halych at the beginning of the XV century. According to a document discovered recently by archivists of the Central State Historical Archive of Ukraine in Lviv (hereinafter - CSHAU in Lviv), in 1400 Svydrygailo provided the village of Studinka (now the village of the same name in the Kalush district of the Ivano-Frankivsk region) and its outskirt to his dependent Hrytsko Kerdyievych. The newly discovered source allows to significantly supplement the information about the influence of the ruler of Podillia on the Halych land, and also records the oldest written mention of the modern city of Kalush.